2023
DOI: 10.3390/sports11030064
|View full text |Cite
|
Sign up to set email alerts
|

Biceps Brachii and Brachioradialis Excitation in Biceps Curl Exercise: Different Handgrips, Different Synergy

Abstract: The current study analyzed the excitation of biceps brachii, brachioradialis, and anterior deltoid during bilateral biceps curl performed with different handgrips. Ten competitive bodybuilders performed bilateral biceps curl in non-exhaustive 6-rep sets using 8-RM with the forearm in supinated, pronated, and neutral positions. The ascending and descending phase of each variation was separately analyzed using the normalized root mean square collected using surface electromyography. During the ascending phase, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Finally, the study revealed that there is a linear correlation between resistance and muscle fatigue [39]. Coratella et al (2023) investigated the impact of different handgrip positions on the activation of the BB and brachioradialis muscles during dumbbell curl exercises. EMG measurements in 10 resistance-trained male subjects revealed that the supinated grip resulted in higher BB activation, while the pronated grip yielded greater brachioradialis activation [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the study revealed that there is a linear correlation between resistance and muscle fatigue [39]. Coratella et al (2023) investigated the impact of different handgrip positions on the activation of the BB and brachioradialis muscles during dumbbell curl exercises. EMG measurements in 10 resistance-trained male subjects revealed that the supinated grip resulted in higher BB activation, while the pronated grip yielded greater brachioradialis activation [40].…”
Section: Introductionmentioning
confidence: 99%
“…Coratella et al (2023) investigated the impact of different handgrip positions on the activation of the BB and brachioradialis muscles during dumbbell curl exercises. EMG measurements in 10 resistance-trained male subjects revealed that the supinated grip resulted in higher BB activation, while the pronated grip yielded greater brachioradialis activation [40]. Typically, the techniques utilized for investigating the mechanical behavior of the BB muscle are contingent upon the particular kind of physical information that researchers seek to acquire.…”
Section: Introductionmentioning
confidence: 99%